The Effect of (c.a.s.e) Model in Mathematics Education at First Intermediate class Students in Mathematic Subject - Hassan Ezat, Hamdi (Opción, 2019)
The objective of the current research is to identify the effect of the c.a.s.e model on the mathematical proficiency of the first grade students in mathematics. The sample consisted of (86) students from the first grade intermediate school in the middle (Qara Quinlo for boys) belonging to the Directorate of Education Kirkuk, 40 students in the experimental group and 46 students in the control group, (K-20) to 0.84. Using the appropriate statistical means, the results showed the superiority of the students of the experimental group studied. Using the appropriate statistical means, the results showed that the students of the group Experimental model (case) on Tal B the control group, who studied in the usual way in the athletic prowess, and in the light of these results, reached a number of conclusions and recommen- dations and proposals.